2-Benzylidenebenzofuran-3(2H)-ones as a new class of alkaline phosphatase inhibitors: synthesis, SAR analysis, enzyme inhibitory kinetics and computational studies. Issue 56 (29th October 2021) - Ashraf, Jamshaid; Mughal, Ehsan Ullah; Alsantali, Reem I.; Sadiq, Amina; Jassas, Rabab. S.; Naeem, Nafeesa; Ashraf, Zaman; Nazir, Yasir; Zafar, Muhammad Naveed; Mumtaz, Amara; Mirzaei, Masoud; Saberi, Satar; et al.
Abstract : Aurones are the plant secondary metabolites belonging to the flavonoid's family. The bioactivities of aurones are very promising, thus these heterocyclic compounds can be considered as an alluring scaffold for drug design and development. Abstract : The excelling role of organic chemistry in the medicinal field continues to be one of the main leads in the drug development process. Particularly, this industry requires organic chemists to discover small molecular structures with powerful pharmacological potential. Herein, a diverse range of chalcone (1–11 ) and aurone (12–22 ) derivatives was designed and synthesized and for the first time, and both motifs were evaluated as potent inhibitors of alkaline phosphatases (APs). Structural identification of the target compounds (1–22 ) was accomplished using common spectroscopic techniques. The effect of the nature and position of the substituent was interestingly observed and justified based on the detailed structure–activity relationship (SAR) of the target compounds against AP. It was concluded from the obtained results that all the newly synthesized compounds exhibit high inhibitory potential against the AP enzyme. Among them, compounds 12 (IC50 = 2.163 ± 0.048 μM), 15 (IC50 = 2.146 ± 0.056 μM), 16 (IC50 = 2.132 ± 0.034 μM), 18 (IC50 = 1.154 ± 0.043 μM), 20 (IC50 = 1.055 ± 0.029 μM) and 21 (IC50 = 2.326 ± 0.059 μM) exhibited excellent inhibitory activity against AP, and even better/more active than KH2 PO4 (standard) (IC50 = 2.80 ± 0.065 μM). Remarkably, compound 20 (IC50 = 1.055 ± 0.029 μM) may serve as a lead structure to design more potent inhibitors of alkaline phosphatase. To the best of our knowledge, these synthetic compounds are the most potent AP inhibitors with minimum IC50 values reported to date. Furthermore, a molecular modeling study was performed against the AP enzyme (1EW2) to check the binding interaction of the synthesized compounds 1–22 against the target protein. The Lineweaver–Burk plots demonstrated that most potential derivative 20 inhibited h-IAP via a non-competitive pathway. Finally, molecular dynamic (MD) simulations were performed to evaluate the dynamic behavior, stability of the protein–ligand complex, and binding affinity of the compounds, resulting in the identification of compound 20 as a potential inhibitor of AP. Accordingly, excellent correlation was observed between the experimental and theoretical results. The pharmacological studies revealed that the synthesized analogs 1–22 obey Lipinski's rule. The assessment of the ADMET parameters showed that these compounds possess considerable lead-like characteristics with low toxicity and can serve as templates in drug design.